2009
DOI: 10.1177/1049732309348368
|View full text |Cite
|
Sign up to set email alerts
|

“Making it All Normal”: The Role of the Internet in Problematic Pregnancy

Abstract: Women are actively encouraged to educate themselves about pregnancy from formal sources (e.g. information leaflets, ante-natal classes, books). In addition, informal stories of pregnancy and birth are routinely told between women. However, increased prenatal testing means that more fetuses are diagnosed with abnormalities, shifting the information requirements during pregnancy. Traditional sources of information cannot cover all possible outcomes, and the internet is beginning to fill this gap. This article dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 18 publications
9
70
0
4
Order By: Relevance
“…Group identification is an essential factor in helping individuals proactively respond to and cope with stigmatizing experiences through examination of the dominant societal discourse and reframing the status in a positive light through self-negotiation (Friedman et al, 2005;Rissel, 1994;van Zomeren, Postmes, & Spears, 2008). Through sharing their experiences, offering and receiving social support, and in finding a common goal, participants gained a more positive self-perception, felt an increased sense of solidarity and empowerment, and benefited from more positive mental health outcomes-findings that are in line with previous research on other stigmatized populations (Latrofa, Vaes, Pastore, & Cadinu, 2009;LeBel, 2008;Lowe, Powell, Griffiths, Thorogood, & Locock, 2009;Wong, Sands, & Solomon, 2010). Reclaiming the word fat was a method by which participants reframed their responses to stigma by changing the power situation in which stigma was allowed to exist (Link & Phelan, 2001), which was done by taking control of the word through a transformation of its negative value into a positive one.…”
Section: Discussionsupporting
confidence: 84%
“…Group identification is an essential factor in helping individuals proactively respond to and cope with stigmatizing experiences through examination of the dominant societal discourse and reframing the status in a positive light through self-negotiation (Friedman et al, 2005;Rissel, 1994;van Zomeren, Postmes, & Spears, 2008). Through sharing their experiences, offering and receiving social support, and in finding a common goal, participants gained a more positive self-perception, felt an increased sense of solidarity and empowerment, and benefited from more positive mental health outcomes-findings that are in line with previous research on other stigmatized populations (Latrofa, Vaes, Pastore, & Cadinu, 2009;LeBel, 2008;Lowe, Powell, Griffiths, Thorogood, & Locock, 2009;Wong, Sands, & Solomon, 2010). Reclaiming the word fat was a method by which participants reframed their responses to stigma by changing the power situation in which stigma was allowed to exist (Link & Phelan, 2001), which was done by taking control of the word through a transformation of its negative value into a positive one.…”
Section: Discussionsupporting
confidence: 84%
“…30,[78][79][80][81] These secondary analyses have led to a number of peer-reviewed publications in leading journals. 35,[82][83][84][85][86][87][88] By bringing together an expert panel of those scholars who have successfully conducted qualitative secondary analysis on the HERG interview collections and other UK data archives, such as the online Economic and Social Data Service (ESDS) Qualidata Archive and the Timescapes Project at the University of Leeds, we aimed to identify practices and principles that would help to promote the sharing and reuse of qualitative data in our field by identifying training needs and providing guidance for academic colleagues who may consider this method for future projects.…”
Section: Introductionmentioning
confidence: 99%
“…The best evidence for the importance of such networks in pregnancy comes from a qualitative study analyzing interviews with 66 women carrying fetuses with diagnosed anomalies (Lowe, Powell, Griffiths, Thorogood, & Locock, 2009). The analysis suggested that women use the Internet to gain understanding of the experiences of others with similar diagnoses, which can provide a framework for coping and decision making that available biomedical information does not offer.…”
Section: The Role Of Social Media In Providing Access To Support and mentioning
confidence: 99%
“…And I felt there were a number of individuals there who were giving good advice and who'd obviously had quite, you know, interesting stories that were relevant. (Lowe et al, 2009(Lowe et al, , p. 1482 Filtered through social media, medical information for pregnant women ''forms an organic, multilayered array'' (Kukla, 2007, p. 28), which includes patient and community voices, along with more traditionally authoritative sources. In the case of VBAC, the Internet offers pregnant women with prior cesarean surgery access to information about the risks and benefits of VBAC.…”
Section: The Role Of Social Media In Providing Access To Support and mentioning
confidence: 99%